Peningkatan Aktivitas Belajar Siswa Melalui Penerapan Model Pembelajaran Discovery Pada Siswa Kelas VIII SMP Negeri 11 Medan - Evi Sahara; Yusni Khairul Amri; Siti Hafni Nasution (PT. ALHAFI BERKAH INDONESIA, 2023)
In the learning activities of SMP Negeri 11 Medan students, there are several problems such as students are less enthusiastic about following the learning process, so that learning activities become unenthusiastic. To overcome this problem, it is necessary to have a learning model that is able to arouse students' enthusiasm for learning. One of the solutions used in this study is the application of the discovery learning model using a scientific approach, this aims to improve student learning activities. This type of research is classroom action research (PTK). The study was conducted in two cycles. The results of this study show that the application of the discovey model can improve student learning activities. The increase can be seen from the results of student learning activities increased from 71.61% in cycle I to 81.37% in cycle II, which means an increase of 9.76%. From the data from the study, it is known that student learning activities in the cognitive and affective aspects of students show a very significant increase from cycle I to cycle II, so the application of learning using the discovery learning model is successful in increasing student enthusiasm for learning.